Implementasi Manajemen Strategik dalam Meningkatkan Minat Peserta Didik Baru di SMPN 3 Cimerak - Rika Yunita (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2025)
This study aims to describe how the implementation of Strategic Management in Increasing the Interest of New Learners at SMPN 3 Cimerak. This research uses descriptive method with qualitative approach. Data collection in this study were interviews, observations and document studies. The data analysis technique used is by reducing data, presenting data and drawing conclusions. to explore the implementation of strategic management at SMPN 3 Cimerak. The results show that the implementation of integrated and measurable strategic management contributes positively to increasing the interest of new students at SMPN 3 Cimerak. The strategic steps implemented by SMPN 3 Cimerak, namely market analysis, identification of school excellence, branding development, digital marketing strategy, collaboration with other parties, and open house program, were analyzed through interviews and direct observation. In-depth analysis of the strategic steps that have been taken reveals the effectiveness of the strategy in attracting new students and strengthening the school's image. Recommendations for future research are to explore other factors that can influence new learners' interest, as well as to evaluate the effectiveness of strategic management strategies over a longer period of time.